The The Evolution of Vertical Video: TikTok and the 21st Century Children's Interactive Learning Trend - Sudarmanto, Joni Agung (Universitas Nahdatul Ulama Surabaya, 2023)
This study tries to discuss how the evolution of vertical video contributes as a learning medium for children in the 21st century. Furthermore, vertical video as learning media refers to the trend of the 21st-century education world, which prioritizes flexibility in learning modes and media. This flexibility also contributes to the increasing massive emergence of contemporary learning media, especially for children, which prioritizes interactivity through the concept of public pedagogy. This study uses a multi-site qualitative. With a literature study of 34 articles covering 21st-century interactive learning from the search databases JSTOR, Taylor Francis, Wiley Library, ScienceDirect, and Google Scholar with keywords: